Evaluation of the Radial Procurvatum Using the Center of Rotation of Angulation Methodology in Chondrodystrophic Dogs - Kwon, Minji; Kwon, Danbee; Lee, Jonghyop; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2022)
To calculate the radial joint orientation angles at frontal and sagittal planes in chondrodystrophic breeds of dogs, including Welsh Corgi, Dachshund, Pekinese, Poodle, Beagle and Maltese by using the center of rotation of angulation (CORA) methodology, and to compare whether there is a statistically significant difference between each breed. Radial joint orientation angles were obtained for eighty-eight dogs, including 23 Welsh Corgis, 16 Dachshunds, 14 Pekinese, 12 Poodles, 10 Beagles and 13 Maltese. Using the CORA methodology, the cranial proximal radial angle (CrPRA) and caudal distal radial angle (CdDRA) in the sagittal plane and medial proximal radial angle (MPRA) and lateral distal radial angle (LDRA) in the frontal plane were measured for six breeds. The mean values of joint angles for each breed were compared to see if any significant differences were observed. The CrPRA, CdDRA, and LDRA mean values of Dachshund and Welsh Corgi breeds were significantly smaller than other breeds, and in MPRA, Pekingese showed significantly smaller values than other breeds. This study confirms that the mean values of radial joint orientation angles can be significantly different among chondrodystrophic breeds. To accurately evaluate the degree of angular deformity of the radius, it may be helpful to refer to the average value for each breed with chondrodystrophy.